ABOUT ALGEBRAIC STRUCTURES AND THEIR RANKS - Tadzhimatova Hosiyatkhon Batirjon qizi; Muhiddinova Umidakhon Bahromjon o’gli (Researchparks Publishing, 2023)
Concepts of group, ring and field, linear space, concepts of algebra and color of algebra were presented, rules, ideas were reviewed.